2013
DOI: 10.1002/nbm.2913
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal 1H MRS of rat forebrain from infancy to adulthood reveals adolescence as a distinctive phase of neurometabolite development

Abstract: The present study represents the first longitudinal, within-subject 1H MRS investigation of the developing rat brain spanning infancy, adolescence, and early adulthood. We obtained neurometabolite profiles from a voxel located in a central location of the forebrain, centered on the striatum, with smaller contributions for cortex, thalamus, and hypothalamus, on postnatal days 7, 35, and 60. Water-scaled metabolite signals were corrected for T1 effects and quantified using the automated processing software LCMod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Although based on the work from Morgan and colleagues [69], the time frame in our study may be sufficient to reflect brain metabolite changes; however, others [70] have shown that in animals born with depletion in omega 3 fatty acids, the effects could possibly be reversed with supplemental diet when the supplementation was given from birth, but when the diet was given starting at weaning, recovery was only partial [70]. The onset of feeding (at weaning) and the duration of the diet (almost 6 weeks) may account for the lack of significant behavioral differences.…”
Section: Discussionmentioning
confidence: 99%
“…Although based on the work from Morgan and colleagues [69], the time frame in our study may be sufficient to reflect brain metabolite changes; however, others [70] have shown that in animals born with depletion in omega 3 fatty acids, the effects could possibly be reversed with supplemental diet when the supplementation was given from birth, but when the diet was given starting at weaning, recovery was only partial [70]. The onset of feeding (at weaning) and the duration of the diet (almost 6 weeks) may account for the lack of significant behavioral differences.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging sequence employed a TE of 13 ms and a TR of 1250 ms. Fifteen transverse slices and seven coronal slices (thickness, 2 mm) were obtained of the rat brain. A 5 × 5 × 5-mm 3 voxel was approximately centered in the brain, with its center a distance of approximately 6 mm from the surface. Effort was made to ensure that the voxel was located in a similar location in each rat, but no segmentation procedures were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy ( 1 H MRS) studies of mouse and rat brain at high magnetic field strengths, such as 9.4 T, have been demonstrated to be useful for the study of a variety of animal models of disease 1 and of brain developmental changes. 2,3 Taurine (Tau) is a relevant brain metabolite in the study of brain tumors, the brain and its development. [4][5][6][7][8] At 9.4 T, the Tau resonance at 3.42 ppm is sufficiently well resolved from other metabolite peaks to be utilized for quantification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent longitudinal magnetic resonance imaging (MRI) study in rats has also identified a peak in cortical thickness during adolescence and a continued increase in volume of cerebral cortex and striatum and myelination from adolescence to adulthood (until PND60) (Mengler et al 2014). Levels of striatal metabolites such as N-acetylaspartate (NAA), glutamate and glutamine have also been observed to increase from neonatal period through adolescence to adulthood as examined in a longitudinal magnetic resonance spectroscopy (MRS) study in rats (Morgan et al 2013). Detailed reviews on maturation of adolescent neuronal systems can be found elsewhere (Brenhouse and Andersen 2011;Lewis 1997;McCutcheon and Marinelli 2009;Spear 2000;Sturman and Moghaddam 2011;Wahlstrom et al 2010).…”
Section: Figure 1-1 Adolescence In Rodents and Neural Maturation Chanmentioning
confidence: 99%